SCI-QOL and WOUND-Q Have the Best Patient-reported Outcome Measure Design: A Systematic Literature Review of PROMs Used in Chronic Wounds - Tert C. van Alphen, MD, MBA; Floor ter Brugge, MD; Emiel L.W.G. van Haren, MD; Maarten M. Hoogbergen, MD, PhD; Hinne Rakhorst, MD, PhD (Plastic and Reconstructive Surgery, Global Open, 2023)
Background:. Chronic wounds are a significant burden on healthcare systems due to high costs of care (2%–4% total healthcare cost) and a considerable burden on patient’s quality of life. Patient-reported outcome measures (PROMs) are questionnaires developed to enable patient self-assessments of their outcomes. A gap in knowledge exists because previous reviews on wound-specific PROMs did not evaluate the quality of the development. The main question is which PROM has the best quality development properties and should be used in clinical care and research. Methods:. PubMed, Embase, and CINAHL were searched from their inception through December 2021. Studies that included patients aged 18 years or older, with chronic wounds, and who reported using a condition-specific PROM for wounds were extracted. We excluded generic PROMs, comments, guidelines, and editorial letters. The COSMIN-guidelines were used to evaluate the quality of the PROMs. Results:. Of the 16,356 articles, a total of 251 articles describing 33 condition-specific PROMs for wounds were used. In total, 17 of 33 (52%) PROMs were developed for specific wound types, and nine of 33 (27%) PROMs were developed for any type of wound. Two of 33 (6%) PROMs were not rated because no development article was available. Only the SCI-QOL (Spinal Cord Injury-QOL) and the WOUND-Q rated “very good” in PROM design. Conclusions:. Thirty-three condition-specific PROMs were found. Only the SCI-QOL and the WOUND-Q rated very good in PROM design. The WOUND-Q is the only condition-specific PROM, which can be used in all types of chronic wounds in any anatomic location.